Microfacies Characterization of Calcareous Crusts and Pleistocene Moghrebian Strata in the Coastal Basin of Tarfaya (Morocco): Paleoclimatic and Paleoenvironmental Implications - Jira, Fatima; Lakhouili, Abdallah (Iraqi Journal of Science, 2024)
Outcrops of detrital sediments dating from the Moghrebian are found in the coastal basin of Tarfaya in southwestern Morocco. These sediments are still little studied and spectacularly extended and surmounted by a hard crust. Our study will focus on three objectives (1) to characterize the microfacies of Moghrebian sediments and to identify their diagenetic evolution, (2) to reconstruct the modalities of development of superficial crusts, and (3) to elucidate the origin of calcium carbonate in these sediments. The results show that the Moghrebian strata have alternating conglomerate beds, lumachel, sandstone, calcarenite, and a well-developed calcareous crust on the surface. The diagenetic evolution of these facies is very early and is characterized by corrosion and isovolumetric epigenesis of quartz by calcite, particularly in the superficial crust. Clay minerals of detrital origin characterize the fine fraction of these sediments. The oversaturation of the environment with calcium carbonate prompted the development of a crust where fibrous clays are newly formed, which reflects the development of climatic conditions with alternating dry and wet seasons in the basin during the post-Moghrebian period.